Industrial Relations and Social Dialogue in the Age of Collaborative Economy (IRDACE). National report: France - Akgüc, Mehtap (Brussels, 2018)
"Online platforms, together with recent developments in technology, have been transforming labour markets and the nature of work. France constitutes an interesting case study for analysing the developments in the platform economy, not only in terms of the laws that directly impact platforms and platform workers, but also as it has been host to new forms of organisations representing platform workers, which attempted direct negotiation with a large and widely known platform.